2017
DOI: 10.1093/cercor/bhx237
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Band Oscillations Preferential for Nociception can be Recorded in the Human Insula

Abstract: Transient nociceptive stimuli elicit robust phase-locked local field potentials (LFPs) in the human insula. However, these responses are not preferential for nociception, as they are also elicited by transient non-nociceptive vibrotactile, auditory, and visual stimuli. Here, we investigated whether another feature of insular activity, namely gamma-band oscillations (GBOs), is preferentially observed in response to nociceptive stimuli. Although nociception-evoked GBOs have never been explored in the insula, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 113 publications
2
50
0
Order By: Relevance
“…Lastly, our results showed that gamma responses, which likely originate from primary somatosensory 11 , 12 and insular 30 cortex, were significantly involved in translating noxious stimuli into motor responses. At first glance, this observation seems to be at variance with previous evidence showing that gamma responses to noxious stimuli are often 10 12 , but not always 10 , 13 , closely related to pain perception.…”
Section: Discussionmentioning
confidence: 57%
“…Lastly, our results showed that gamma responses, which likely originate from primary somatosensory 11 , 12 and insular 30 cortex, were significantly involved in translating noxious stimuli into motor responses. At first glance, this observation seems to be at variance with previous evidence showing that gamma responses to noxious stimuli are often 10 12 , but not always 10 , 13 , closely related to pain perception.…”
Section: Discussionmentioning
confidence: 57%
“…Nevertheless, some studies have suggested that lesions of the insula impair the ability to perceive pain and that direct cortical stimulation of the insula or epileptic activity in the insula can generate pain, although only in rare cases ( Isnard et al , 2011 ; Mazzola et al , 2012 ). Furthermore, intracerebral recordings of local field potentials in the human insula have shown that painful heat stimuli elicit gamma-band oscillations that are not observed in response to similarly salient tactile, auditory or visual stimuli ( Liberati et al , 2018 ) ( Fig. 1 ).…”
Section: Pain-specific and Pain-selective Brain Activitymentioning
confidence: 99%
“…Similarly, although the insula has been proposed to be strongly involved in pain perception, equally salient nociceptive and non-nociceptive stimuli trigger similar local field potentials (LFPs) recorded directly within the insula ( Liberati et al , 2016 ). Nevertheless, other less prominent features of the sampled activity might be more selective for pain or nociception, as reflected by the selective increase of gamma-band oscillations (GBOs) when painful heat stimuli are presented ( Liberati et al , 2018 ). BOLD = blood-oxygen level-dependent; ER% = event-related change in oscillation amplitude; ERP = event-related potential.…”
Section: Introductionmentioning
confidence: 99%
“…Similar pathways have been demonstrated by neuroimaging studies in humans ( Brooks and Tracey, 2005 ; Omori et al, 2013 ). Human neurophysiological studies have also revealed nociceptive responses within SI, SII, insular and cingulate cortices ( Frot et al, 2001 , 2013 , 2014; Liberati et al, 2017 ). Lesions and electrical stimulation in these cortical regions as well as strokes involving the spinothalamic tract in the internal capsule have together confirmed a role of this cortical network in human pain awareness ( Ballantine et al, 1967 ; Berthier et al, 1988 ; Kim, 1992 ; Cereda et al, 2002 ; Torta et al, 2013 ; Boccard et al, 2014 , 2017 ; Hirayama et al, 2014 ; Russo and Sheth, 2015 ; Agarwal et al, 2016 ; Denis et al, 2016 ; Wang et al, 2017 ).…”
Section: Localization Of Pain Awareness In the Human Brainmentioning
confidence: 99%